Passenger Data Collection and Goods Distribution Using Web-Based Cash Basis Method at PT Murni Trans - Sulis Minandar; Ruly Dwi Arista; Suheri (Cattleya Darmaya Fortuna, 2026)
This study aims to design and develop a web-based system for passenger data management and goods distribution at PT Murni Trans by applying the cash basis method in financial recording. The problem faced by the company is that data and transaction recording are still carried out manually, which may lead to errors, delays in reporting, and difficulties in monitoring cash flow in real time. The method used in this research is the cash basis method, where revenue is recognized when cash is received. The system is developed as a web-based application to facilitate the management of passenger data, goods delivery, and transaction recording in an integrated manner. The data used include passenger data, goods data, and transaction data stored in a database.The results show that the developed system improves efficiency in data management, accelerates transaction recording processes, and produces more accurate and easily accessible financial reports. Based on the cash basis calculation, the total revenue generated by the company is IDR 5,095,000. Therefore, the implementation of a web-based system using the cash basis method can help PT Murni Trans improve operational performance and financial management effectively and efficiently.